Evaluation of the Effectiveness of Rehabilitation in Rowers-Paraolympians With the Use of Computer Rapid Diagnosis Nakatani on the Complex “Mediscreen” - G.G., Apriamashvili; R.Ya., Tatarintseva; N.N., Omelchuk; I.E., Grigoryan; N.M., Ezhova; P.F., Ezhov (Pharmacognosy Communications)
Background: Effective health monitoring relied on the speed of execu- tion, the reliability of the results, high performance, effectiveness, safety, ease of use, low cost, reliability, the possibility of mass production, tech- nology, and much more. Methods: Usage of the Nakatani method on the “Mediscreen” equipment, evaluated the effectiveness of integrated methods of rehabilitation of Paralympic rowers to determine functional complaints as harbingers of organic changes in the body. Results: The results of survey conducted with usage of Mediscreen are easily reproducible, absolutely repeatable and stable.
Keywords: Effectiveness of rehabilitation; Paralympian’srowers; Express Nakatani; Complex “Mediscreen”